P01.131 Non-invasive detection ofIDH-wildtype genotype in gliomas using dynamic18F-FET-PET. (19th September 2018) - Suchorska, B; Vettermann, F; Unterrainer, M; Nelwan, D; Forbrig, R; Dorostkar, M; Kreth, F W; Bartenstein, P; Tonn, J C; Albert, N
Abstract: Background: Gliomas with an isocitarate dehydrogenase ( IDH ) wildtype (wt) status have a dismal prognosis comparable to glioblastoma as reflected by the 2016 revision of the WHO classification of gliomas. In order to ensure timely adjustment of surgical and adjuvant treatment strategy, demand for non-invasive imaging methods is high. 18 F-FET-PET has been shown to be an important diagnostic tool for glioma management, delivering information on prognosis and therapy response. Aim of this study was to evaluate dynamic 18 F-FET-PET for non-invasive evaluation of IDH wt status prior to therapy. Material and Methods: 341 patients with WHO II-IV glioma were included, in whom IDH mutation status, MRI and dynamic 18 F-FET-PET scans were available at initial diagnosis prior to any further therapy. We assessed sensitivity, specificity, accuracy and positive as well as negative predictive values for maximal tumour-to-background ratio (TBRmax ) and minimal time-to-peak (TTPmin ) for prediction of IDH wt status in the entire group as well as in the subgroup of non-contrast enhancing (non-CE) tumors. Results: Molecular analyses revealed 178 IDH mutant and 163 IDH wt tumors; 270 patients were classified as FET-positive, in these cases, TTP analysis was performed. Median TBRmax in IDH wt gliomas was 3.1 compared to 2.8 in IDH mutant tumors (p=<0.01). ROC-analyses revealed no reliable cut-off using TBRmax, due to high overlap of the two groups. In contrast, searching for a threshold in dynamic analysis, TTPmin ≤ 12.5 minutes identified IDH wt gliomas with a high positive predictive value (accuracy: 79%, PPV: 87%; NPV: 72%). In the subgroup of non-CE glioma in MRI (n=161), IDH wt genotype was identified with an accuracy of 84% (PPV 83%, NPV: 84 %). Conclusion: Dynamic 18 F-FET PET using TTPmin analysis provides a reliable non-invasive method for detection of IDH wt genotype especially in tumors without CE on MRI and can help to identify high-risk patients prior to treatment initiation.